KAP ANALYSIS OF NURSES REGARDING PREVENTION OF OSTEOPOROSIS AND ITS ASSOCIATION WITH NUTRITIONAL BEHAVIORS - SULTANA, M; SAMUAL, S; SARDAR, M (Biological and Clinical Sciences Research Journal, 2024)
Osteoporosis is a significant public health concern, affecting millions globally. Nurses play a vital role in educating and guiding patients about preventive measures. However, their knowledge, attitudes, and practices (KAP) regarding osteoporosis prevention, along with their own nutritional behaviours, are crucial factors that can influence patient care and health outcomes. Objective: To determine the knowledge, attitudes, and practice of nurses regarding osteoporosis prevention and its association with nutritional behaviours. Methods: A cross-sectional study was conducted in the Nursing Department of Nishtar Hospital, Multan from September 2023 to August 2024. A total of 100 nurses with at least a bachelor’s degree and a minimum of one year of work experience were included in the study. The data was collected through a questionnaire divided into five sections to collect demographic information, levels of knowledge, attitudes and practices, and nutritional habits of nurses. Results: The mean knowledge score was 19.24 ± 4.10 with 55% of nurses possessing good knowledge. The mean attitude score was 71.68 ± 7.05 with 80% of nurses having positive attitudes. The mean attitude score was 47.32 ± 7.44 with 58% of nurses having good practices. 58% of nurses had good nutritional behaviours with a mean score of 111.08 ± 14.73. A strong direct association was observed between nutritional behaviors and KAP scores (p=0.001). Conclusion: Good knowledge, attitudes, practices, and nutritional behaviours were noted in nurses regarding osteoporosis prevention. The KAP scores had a direct and strong association with nutritional behaviors promoting lifestyle changes.